An unusual cause of heart failure in postoperative tetralogy of Fallot - Gurbhej Singh; Arun Gopalakrishnan; Sivasubramonian Sivasankaran (Wolters Kluwer Medknow Publications, 2022)
The long-term results of transatrial transpulmonary tetralogy of Fallot (TOF) repair have been excellent. Progressive pulmonary regurgitation and consequent right ventricular (RV) dilatation are the most common long-term sequel of definitive repair in childhood. Overt systemic venous congestion after TOF repair is limited to the rare setting where RV dysfunction sets in due to deferred surgery or progressive arrhythmia. Here, we report a unique case of right heart failure from an unexpected etiology, 28 years after TOF repair. Cardiac catheterization confirmed findings of elevated right heart pressures. Magnetic resonance imaging showed obliteration of the RV apex with late gadolinium enhancement of the right ventricular apical endomyocardium.